2008
DOI: 10.1007/s10508-008-9346-9
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effects of Acute Alcohol Intoxication on Sexual Risk-taking: The Roles of Subjective and Physiological Sexual Arousal

Abstract: Three experiments supported the idea that alcohol fosters sexual risk-taking in men and women, in part, through its effects on sexual arousal. In Experiment 1, increasing alcohol dosage (target blood alcohol levels of .00, .04, .08%) heightened men's and women's risk-taking intentions. Alcohol's effect was indirect via increased subjective sexual arousal; also, men exhibited greater risk-taking than women. In Experiment 2, an extended dosage range (target blood alcohol levels of .00, .06, .08, .10%) heightened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
171
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(190 citation statements)
references
References 57 publications
14
171
5
Order By: Relevance
“…One of the strengths of experimental methods is the capacity to capture in-the-moment mechanisms that may play a crucial role in the moments preceding a risky sexual decision (George et al, 2009). In particular, alcohol administration experiments have provided evidence that perceptions of two acute states-level of intoxication and level of sexual arousal-play an important role in alcohol's effects on risky sexual intentions.…”
Section: Alcohol's Effects On Sexual Risk Takingmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strengths of experimental methods is the capacity to capture in-the-moment mechanisms that may play a crucial role in the moments preceding a risky sexual decision (George et al, 2009). In particular, alcohol administration experiments have provided evidence that perceptions of two acute states-level of intoxication and level of sexual arousal-play an important role in alcohol's effects on risky sexual intentions.…”
Section: Alcohol's Effects On Sexual Risk Takingmentioning
confidence: 99%
“…Three separate studies have investigated the joint infl uence of being both sexually aroused and intoxicated (Abbey et al, 2005;George et al, 2009;MacDonald et al, 2000). Abbey et al (2005) found that men's and women's perceived sexual arousal predicted their risky sex intentions over and above alcohol's effects.…”
Section: Alcohol's Effects On Sexual Risk Takingmentioning
confidence: 99%
“…The acute effects of alcohol can also increase risk-taking behavior by narrowing an individual's focus to only the most salient cues in the environment, a process referred to as alcohol myopia (Steele and Josephs, 1990;Taylor and Leonard, 1983). In a sexual encounter involving alcohol, the most salient cue may be sexual arousal rather than the potential risk associated with a sexual partner (e.g., Davis et al, 2007;George et al, 2009;MacDonald et al, 2000), thereby increasing the likelihood of risk-taking behavior (Adefuye et al, 2009).…”
mentioning
confidence: 99%
“…Literature has accumulated much evidence about the effects of alcohol on social behavior and emotions, which vary widely and are highly irregular (Davis, Hendershot, George, Norris, & Heiman, 2007;George et al, 2008;Phillips & Giancola, 2008). Therefore, acute alcohol intoxication can both increase aggressive (Zeichner & Pihl, 1980) and enhance altruistic (Levenson, Sher, Grossman, Newman, & Newlin, 1980) behaviors or even reduce anxiety states (Levenson et al, 1980), among other behavioral effects.…”
Section: Alcohol Myopia Theorymentioning
confidence: 99%
“…In addition to the violent behavior, the alcohol consumption among adolescents is also related to risky sexual behavior (Davis et al, 2007;George et al, 2008;and MacDonald et al, 1996). Intoxicated volunteers are more susceptible to environmental cues inducing to unsafe sexual practice compared to sober individuals.…”
Section: Risky Behavior Under the Perspective Of Alcohol Myopiamentioning
confidence: 99%